Students’ English Speaking Anxiety Based on Personality Traits for Islamic Boarding School - Kurniasy, Dessy; Susan, Rianty (JL3T (Journal of Linguistics, Literature and Language Teaching), 2019)
This study was carried out to investigate English speaking anxiety experienced by students based on their personality traits (extrovert-introvert dimension) in boarding school. The method used in this study was quantitative approach with descriptive design. The population in this study were 120 students in the fifth grade student of MUQ Langsa where 92 students as the sample taken by using random sampling technique. The data were collected by “Mark Parkinson (1997) Personality Questionare” that consists of 16 statements and “Foreign Language Classroom Anxiety Scale (FLCAS)” by horwitz. et.al (1986) that consists of 33 statements. The finding indicated that the percentage of students who exhibit each dimension of personality from the highest to the lowest; they were introvert dimension (ID) of personality 67,4% and extrovert dimension (ED) of personality 32,6 %. The result of English Speaking Anxiety level divided into five categories. There were 11 students or 12 % in low level, 32 students or 34,8 % in medium level, 47 students or 51,1 % in high level, 2 students or 2,2 % in very high level and there was no one in very low level of the English speaking anxiety. Based on these finding it can be concluded that English speaking anxiety of the students was high level range and introvert was the dominant personality dimension possessed by the students.